Levels of vaccination coverage among HIV-exposed children in China: a retrospective study - Rui Shen; Ai-Ling Wang; Xiao-Ping Pan; Ya-Ping Qiao; Qian Wang; Xiao-Yan Wang; Shui-Ling Qu; Tong Zhang (BMC, 2021)
Abstract Background Vaccination is crucial for human immunodeficiency virus (HIV)-exposed children because of their increased risk of morbidity and mortality from various vaccine-preventable diseases. However, studies have shown that they are at high risk of incomplete vaccination. Although China has developed prevention of mother-to-child transmission (PMTCT) of HIV programs substantially over the past decades, few studies have investigated the immunization levels of Chinese HIV-exposed children. Therefore, we aimed to evaluate vaccination coverage and its associated factors among HIV-exposed children in China during 2016‒2018. Methods We conducted a retrospective cohort review of all cases of Chinese HIV-exposed children born between July 1, 2016 and June 30, 2018 recorded in the Chinese information system on PMTCT. The vaccination coverage indicators refer to the percentage of children who received recommended basic vaccines, including Bacillus Calmette-Guérin (BCG), hepatitis B (HepB), polio, measles-containing vaccine (MCV), and diphtheria-tetanus-pertussis-containing (DTP) vaccine. Univariate and multivariate logistic regression analyses expressed as crude odds ratios (cORs) and adjusted odds ratios (aORs), each with 95% confidence intervals (95% CI), were performed to compare the proportional differences of factors associated with vaccine coverage. Results Among the enrolled 10 033 children, the vaccination rate was 54.1% for BCG, 84.5% for complete HepB vaccination, 54.5% for complete polio vaccination, 51.3% for MCV, and 59.5% for complete DTP vaccination. Children with perinatally acquired HIV (PHIV) were 2.46‒3.82 times less likely to be vaccinated than HIV-exposed uninfected children. Multivariate logistic regression indicated that children of Han ethnicity (aOR = 1.33‒2.04), children with early infant diagnosis (EID) of HIV (aOR = 1.86‒3.17), and children whose mothers had better education (college or above, aOR = 1.63‒2.51) had higher odds of being vaccinated. Most of the deceased children (aOR = 4.28‒21.55) missed vaccination, and PHIV (aOR = 2.46‒3.82) significantly affected immunization. Conclusions Chinese HIV-exposed children had low vaccination coverage, which is a serious health challenge that needs to be addressed thoroughly. Interventions should be developed with a focus on minority HIV-exposed children whose mothers do not have formal education. Particularly, more attention should be paid to EID to increase access to immunization. Graphical abstract